ANALYSIS OF ABDULLAH SAEED'S CONTEXTUAL INTERPRETATION IN QS. ALI IMRAN VERSE 159 CONCERNING PARENTING PATTERNS FOR CHILDREN - Asiah, Siti; Shalihah, Imraatus (Alif Lam : Journal of Islamic Studies and Humanities, 2024)
This study analyzes Abdullah Saeed's contextual interpretation of QS. Ali Imran verse 159 with a focus on parental upbringing. Abdullah Saeed, a contemporary Islamic intellectual, emphasizes the need for a contextual approach in understanding the verses of the Qur'an to make them relevant to modern conditions. QS. Ali Imran verse 159, which speaks of the Prophet Muhammad's gentle and consultative approach with his companions, is used as a basis to examine principles of wise and compassionate parenting. This study employs a descriptive qualitative method with a literature review approach and aims to explore the relevance of the values contained in the verse to the challenges of parenting in the digital age. The results show that a contextual interpretation can provide comprehensive guidance for parents in building harmonious relationships and educating children with a gentle, wise, and consultative approach.